1987
DOI: 10.1139/y87-164
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of potassium homeostasis in the mammalian nervous system

Abstract: Double-barrelled ion-sensitive microelectrodes were used to measure changes in the intracellular activities of K+, Na+, and Cl− (aKi, aNai, aCli) in neurones of rat sympathetic ganglia and in glial cells of slices from guinea-pig olfactory cortex. In sympathetic neurones, carbachol and γ-aminobutyric acid (GABA) produced a reversible decrease of aKi. The decrease of aKi during carbachol was accompanied by a rise of aNai, whereas in the presence of GABA decreases of aKi and aCli were seen. The reuptake of K+ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…We must, however, emphasize that different clearance mechanisms may dominate in other brain regions. Increased Na 1 /K 1 -ATPase activity generates intracellular K 1 accumulation and its molecular characteristics therefore aligns well with the reported transient increase in intracellular K 1 concentration of astrocytes during the burst of activity which, however, is immediately followed by post-stimulus restoration of neuronal [K 1 ] i Grafe and Ballanyi, 1987). The a2b2 isoform constellation characteristic to Na 1 /K 1 -ATPase in glial cells appears to be specifically geared to respond to excess extracellular K 1 due to its lower K 1 affinity and higher voltage-sensitivity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We must, however, emphasize that different clearance mechanisms may dominate in other brain regions. Increased Na 1 /K 1 -ATPase activity generates intracellular K 1 accumulation and its molecular characteristics therefore aligns well with the reported transient increase in intracellular K 1 concentration of astrocytes during the burst of activity which, however, is immediately followed by post-stimulus restoration of neuronal [K 1 ] i Grafe and Ballanyi, 1987). The a2b2 isoform constellation characteristic to Na 1 /K 1 -ATPase in glial cells appears to be specifically geared to respond to excess extracellular K 1 due to its lower K 1 affinity and higher voltage-sensitivity.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, regulation of extracellular K + concentration ([K + ] o ) is of vital importance for neuronal function. In vitro studies have shown that stimulation-induced increases in [K + ] are paralleled by accumulation of K + in astrocytes, suggesting an astrocytic contribution to [K + ] o regulation (Ballanyi et al 1987; Grafe and Ballanyi 1987). Neuronal activity is, in addition, associated with shrinkage of the extracellular space (Dietzel et al 1980; Ransom et al 1985) probably due to astrocytic swelling (MacVicar et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that the b-wave is the extracellular expression of radial current flow generated by a potassium-mediated depolarization of the Muller cells (28)(29)(30) (38,39). Both the permeability of the cell membrane to potassium and energydependent processes are thought to participate in maintaining the stability ofthe extracellular potassium concentration (40). The glial cell reaction to the neuronal release of GABA may represent another component in this homeostatic system.…”
Section: Resultsmentioning
confidence: 99%
“…The neighbouring astrocytes act as temporary K + sinks primarily via the action of the Na + /K + ‐ATPase and, to a smaller extent, the K + channel Kir4.1 (Ballanyi et al . ; Grafe & Ballanyi, ; Ransom et al . ; Kofuji & Newman, ; MacAulay & Zeuthen, ; Larsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The neighbouring astrocytes act as K + sinks during neuronal activity and take up a portion of the neuronally‐released K + (Ballanyi et al . ; Grafe & Ballanyi, ), predominantly via the glia‐specific K + ‐sensitive α2β2 isoform combination of the Na + /K + ‐ATPase, which is kinetically geared to respond to increased [K + ] o and the associated membrane depolarization (Ransom et al . ; D'Ambrosio et al .…”
Section: Introductionmentioning
confidence: 99%